(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This research paper describes various composite materials reinforced with hybrid biofibers. Due to their low cost, availability, ease of production and high environmental friendliness, hybrid biofiber composites were chosen to study the reinforcing potential of various formulations using composites. Further research is being conducted worldwide to improve the thermal, tribological and mechanical properties of these engineered biocomposites, and their potential has been demonstrated in a wide range of applications. This review aims to provide an overview of the factors influencing the mechanical performance of natural hybrid biofiber-reinforced composites and the advances achieved through them.